KAMUS DIGITAL TANAMAN OBAT MENGGUNAKAN ALGORITMA ROCCHIO BERBASIS MOBILE - Arie Qurania (Ilmu Komputer, FMIPA, Universitas Pakuan, 2020)
Medicinal plants are known since the days of ancestors used as natural ingredients for various diseases such as diarrhea, colds, hypertension, diabetes, malaria, dengue fever, stomach ache, intestinal inflammation, cholesterol, and toothache. Medicinal plants can not replace the existence of medical drugs that have been clinically tested but the efficacy of medicinal plants can be used as an alternative treatment. Medicinal plants can be used in several parts of the plant, including leaves, stems, tubers, fruit, roots, and bark. Society generally knows the efficacy and how to mix medicinal plants from the experience of previous parents or through books and writings. Search through books or writings requires a short time compared to searches through digital media such as mobile phones. The research aims to create a digital dictionary of mobile-based medicinal plants which has a search facility based on the words entered, for example, the contents of the medicinal plants. Digital dictionary application of medicinal plants using the pecarian technique with Rocchio algorithm with a total data of 200 medicinal plants.KAMUS DIGITAL TANAMAN OBAT MENGGUNAKAN ALGORITMA ROCCHIO BERBASIS MOBILE